The hobbit or there and back again - Tolkien, J. R. R. (John Ronald Reuel) 1892-1973 (Houghton Mifflin Harcourt, 2012)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.